Evaluation of a monoglyceride for antimicrobial activity against Gram-positive and -negative bacteria. Issue 5 (27th May 2022) - Ukachukwu, Faith; Alany, Raid; Snyder, Lori
Abstract : Background: The Gram-positive bacterium Staphylococcus aureus, and Gram-negative Neisseria gonorrhoeae and Pseudomonas aeruginosa bacteria, have developed multi-drug resistance to currently recommended antibiotic treatment resulting in worse clinical outcomes and significant economic burden. N. gonorrhoeae causes the sexually transmitted infection gonorrhoea and S. aureus and P. aeruginosa causes nosocomial infections including a plethora of infections that affect the skin, lungs, heart, eyes, ears, bones, and blood. Novel therapies are desperately needed to replenish the clinical pipeline as current antibiotic treatments fail. Methods: Monolaurin was investigated against strains of N. gonorrhoeae, S. aureus and P. aeruginosa. The minimum inhibitory concentration of monolaurin was determined by agar diffusion assay for N. gonorrhoeae and broth microdilution assay for S. aureus and P. aeruginosa. Bactericidal activity of monolaurin was assessed in log reduction assay and the time - kill activity of various concentrations of the monoglyceride was evaluated over 5 hours. At least 4 log10 killing activity was considered bactericidal. Result: Monolaurin inhibited growth ofS. aureus, N. gonorrhoeae, and P. aeruginosa at a range of 0.1mM - 3.13mM concentrations. At 1.5mM concentration, monolaurin killed S. aureus and N. gonorrhoeae at 180 minutes and 60 minutes, respectively. Monolaurin at 3mM concentration rapidly killed N. gonorrhoeae within 2 minutes while 25mM concentration killed P. aeruginosa within 60 minutes. Conclusion: The evidence suggests that monolaurin actively killed Gram-positive and remarkably Gram-negative bacteria. This monoglyceride can potentially be developed as an antimicrobial therapy against these bacterial infections and may prove useful when coinfection with P. aeruginosa and S. aureus are present.